@Naganite I don't have a full answer to this, but maybe a useful comment: If you have a quadratic polynomial $X^2+pX+q$, you can substitute $X\mapsto X-\frac{p}{2}$ to bring it to the form $X^2+(q-\frac{p^2}{4})$. This substitution is precisely done so that the $X$ terms cancel out. Similarly, if you have a cubic $X^3+aX^2+bX+c$, you can substitute $X\mapsto X-\frac{a}{3}$ to get the cubic $X^3+(b-\frac{a^2}{3})X+(\frac{2a^3}{27}-\frac{ab}{3}+c)$. Indeed, there is a pattern here. If you have a monic polynomial of degree $n$, substitute $X\mapsto X-\frac{a}{n}$, where $a$ is the coefficient …